Comparison of Two Viewing Methods for Estimating Largemouth Bass and Walleye Ages from Sectioned Otoliths and Dorsal Spines. (30th October 2017) - Wegleitner, Eric J.; Isermann, Daniel A.
Abstract: Many biologists use digital images for estimating ages of fish, but the use of images could lead to differences in age estimates and precision because image capture can produce changes in light and clarity compared to directly viewing structures through a microscope. We used sectioned sagittal otoliths from 132 Largemouth Bass Micropterus salmoides and sectioned dorsal spines and otoliths from 157 Walleyes Sander vitreus to determine whether age estimates and among‐reader precision were similar when annuli were enumerated directly through a microscope or from digital images. Agreement of ages between viewing methods for three readers were highest for Largemouth Bass otoliths (75–89% among readers), followed by Walleye otoliths (63–70%) and Walleye dorsal spines (47–64%). Most discrepancies (72–96%) were ±1 year, and differences were more prevalent for age‐5 and older fish. With few exceptions, mean ages estimated from digital images were similar to ages estimated via directly viewing the structures through the microscope, and among‐reader precision did not vary between viewing methods for each structure. However, the number of disagreements we observed suggests that biologists should assess potential differences in age structure that could arise if images of calcified structures are used in the age estimation process. Received May 26, 2017; accepted September 19, 2017Published online October 30, 2017